Contemporary Challenges of Democratisation and Development in Africa - Olayode, Kehinde (European Scientific Journal, ESJ, 2016)
The end of the cold war and the triumph of liberalism after the collapse of the Soviet Union had a reverberating effect on the wave of democratisation that swept through most parts of the developing world, including Africa. In spite of the euphoria of the third wave of democratisation, the economic condition in Africa looks grim. Africa’s traditional importance as a supplier of raw materials has diminished with competition from synthetic substitute and suppliers in Asia, Latin America and the former Soviet Republics. Also, in the current wave of massive capital movements to the ‘emerging markets’, Africa remains marginal. The paper argues that while democracy is usually seen as a ‘harbinger of development’, it is also recognised that the enthronement of democracy becomes more improbable in a harsh economic environment. This is to say that while democracy enhances development, it is in itself distressed by acute poverty, which threatens the very survival of individuals. While transitions towards democracy do not guarantee rapid economic development and improved human right situations, democracy should however create a window of opportunity where groups struggling for development and human rights would have better possibilities than before for realising their demands. Concluding, any efforts by Western donor countries or the IMF and the World Bank to impose political conditionality to encourage democratisation in Africa will result in mere window dressing. There is also the possibility of unstable democracies arising from a conflict between those who want to complete the democratisation process and those who want to halt it for failing to deliver the much-desired goods. The paper is a review of dynamism of contemporary democratic movements amidst different challenges in Africa. It is undertaken exploring different perspectives through desk review, theoretical interrogations and analysis of relevant data.